2000
DOI: 10.1007/s004550010006
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and Acoustic Signals Associated with Bolus Passage during Swallowing

Abstract: In order to advance our understanding of the relation between respiration and deglutition, simultaneous videofluoroscopy and respirodeglutometry was performed. Fifteen normal, healthy, young adults (20-29 years of age) were connected to a respirodeglutometer and positioned for simultaneous videofluoroscopic assessment in the lateral plane. Subjects performed three swallows each of a 5-ml and a 10-ml bolus of liquid barium and a 5-ml bolus of paste barium, for a total of nine swallows per subject. Location of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
2
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 32 publications
9
64
2
5
Order By: Relevance
“…Seemingly contrary to the findings of the current study, Perlman, Ettema, and Barkmeier (2000) reported that no significant temporal differences of seven different respiration and swallowing variables were observed as a function of viscosity in 15 young adults. The difference in findings relative to viscosity between the present study and that of Perlman and colleagues is that they were not specifically investigating SA onset relative to lingual bolus propulsion via lingual manometry.…”
Section: Discussioncontrasting
confidence: 56%
“…Seemingly contrary to the findings of the current study, Perlman, Ettema, and Barkmeier (2000) reported that no significant temporal differences of seven different respiration and swallowing variables were observed as a function of viscosity in 15 young adults. The difference in findings relative to viscosity between the present study and that of Perlman and colleagues is that they were not specifically investigating SA onset relative to lingual bolus propulsion via lingual manometry.…”
Section: Discussioncontrasting
confidence: 56%
“…A duração maior da apneia nas deglutições de saliva encontrada no presente estudo pode se dever ao fato de que essas deglutições originaram, no geral, registros de baixa intensidade, inclusive para os sons da respiração, que, quanto mais próximos do início da deglutição perdem intensidade significativamente, dificultando, em alguns casos, o estabelecimento exato da interrupção da respiração. Estudos que realizaram a análise do fluxo aéreo durante a deglutição, mais precisas do que as obtidas no presente estudo, revelaram durações menores, provavelmente representando melhor a realidade existente na população (6,20,21) . Outro estudo, no qual videodeglutogramas associados à monitoração do fluxo aéreo nasal foram realizados, encontrou apneias da deglutição maiores que aqueles mensuradas no presente trabalho, com duração média de 2 segundos (7) .…”
Section: Discussionunclassified
“…Em contraponto, outros autores, em estudo videofluoroscópi-co, notaram que o tempo de trânsito faríngeo não aumentou com o avanço da idade. Os autores acreditam que o tempo prolongado de trânsito faríngeo observado em outros estudos, pode estar mais relacionado a comorbidades do que à idade dos sujeitos (6) .…”
Section: Discussionunclassified
See 2 more Smart Citations